POLA RELASI SUAMI ISTRI SEBAGAI UPAYA MENINGKATKAN KELANGGENGAN PERKAWINAN - Sandy Diana Mardlatillah; Nurus Saadah (Sociocouns: Journal of Islamic Guidance and Counseling, 2022)
The husband and wie relationship is one of the foundations and determines the pattern for the whole relationship in the family. The problem of poor husband and wife relations resulted in many families being separated or falling apart and failure. Fostering a husband and wife relationship is a very important element in the longevity of a marriage. One of the keys to the longevity of a marriage is success in making adjustments between the two. Adjustment is dynamic and a way of thinking that is not rigid. The method used in this study is a literature review. The results of this study are the pattern of husband and wife realtioons in marriage, namely owner-prooperty, head-complement, senior-junior partner, and equal partner. There are two other relationship patterns, namely the division of labor in the domestic area, while the second is done flexibly according to the agreement, the division of tasks between husband and wife. In additioon, there are other aspects in building family harmony with openness between the two, mutual trust, mutual understanding and continuous communication.